2012
DOI: 10.1111/j.1365-2621.2012.03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, phenolic and anthocyanin contents of various rhubarb (Rheum spp.) varieties

Abstract: Summary Antioxidant activity (ABTS assay), total phenolics and total anthocyanins were determined in the petioles of twenty‐nine rhubarb (Rheum spp.) varieties. Antioxidant activity ranged from 463 ± 50 (Rheum officinale) to 1242 ± 2 μmol Trolox per g DW (Valentine). The phenolic content varied from 673 ± 41 (Loher Blut) to 4173 ± 23 mg GAE/100 g DW (Plum Hutt) and had a low correlation (r = 0.663) with antioxidant results. Seven of the varieties (Plum Hutt, Valentine, Minnesota No. 8, Cherry Red, Cawood Delig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
(46 reference statements)
2
27
0
Order By: Relevance
“…anthocyanins were determined in the petioles of twenty-nine rhubarb (Rheum spp.) varieties In result identified that antioxidant activity ranged from 463±50 (Rheum officinale) to 1242±2 μmol Trolox/g, the phenolic content varied from 673±41 (Loher Blut) to 4173±23 mg GAE/100 g. The percentages of two main anthocyanins in rhubarb, cyanidin 3-glucoside and cyanidin 3-rutinoside varied from 66.07:33.93, respectively, in Valentine to 9.36:90.64, respectively in R. officinale (Takeoka et al, 2013).…”
mentioning
confidence: 87%
“…anthocyanins were determined in the petioles of twenty-nine rhubarb (Rheum spp.) varieties In result identified that antioxidant activity ranged from 463±50 (Rheum officinale) to 1242±2 μmol Trolox/g, the phenolic content varied from 673±41 (Loher Blut) to 4173±23 mg GAE/100 g. The percentages of two main anthocyanins in rhubarb, cyanidin 3-glucoside and cyanidin 3-rutinoside varied from 66.07:33.93, respectively, in Valentine to 9.36:90.64, respectively in R. officinale (Takeoka et al, 2013).…”
mentioning
confidence: 87%
“…TNF-α plays important roles in the development of intractable stomatitis such as RAS and OLP [15,16] . Artemisia capillaris flower, gardenia fruit, and rhubarb have antioxidant activity [14,[17][18][19][20][21] . In particular, gardenia fruit induces the expression of NF-E2 related factor 2 (Nrf2) mRNA, which is followed by an upregulation of antioxidant response element (ARE)-mediated genes such as heme oxygenase-1 (HO-1) [22][23][24][25] .…”
Section: Etiopathogenesis Of Intractable Stomatitis and The Action Mementioning
confidence: 99%
“…They are a natural dye of plant origin and have a lot of health-promoting properties, among other things: they protect tissue against excessive UV radiation (Gawałek et al 2017). Nowadays they are more and more often used in pharmaceutical and cosmetic industry (Takeoka et al 2013). The presence of anthocyanin compounds in rhubarb is used for effective treatment of cancer cells by its antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%